O USO DO ETORICOXIBE OU DE DEXAMETASONA PARA PREVENÇÃO E CONTROLE DA DOR PÓS OPERATÓRIA EM CIRURGIAS MUCOGENGIVAIS - Zardo, Ligia Nadal (2012)
The aim of this study was to compare the use of etoricoxib and dexamethasone for the prevention and control of postoperative pain in mucogingival surgery. Fifty-eight patients took part in this randomized parallel double- blind clinical trial. Patients who had at least one area with indication for mucogingival surgery, such as narrow width and thickness of keratinized tissue, labial frenum with an insertion close to the gingival margin, shallow depth of the vestibule and Miller`s Class I and II gingival recession with aesthetic complain were included in the study and were randomly divided into 3 groups (G): G1 – placebo 1h before surgery; G2 – 8mg dexamethasone 1h before surgery; G3 – 90mg etoricoxib 1h before surgery. Pain intensity was assessed in the donor and receptor area separately using the numerical rating scale NRS – 101, every hour for the first 8 hours after surgery and three times a day within 3 days. Rescue medication (paracetamol 750mg) was provided to be used in case of pain. The results showed that there was a statistically significant difference in the intensity of postoperative pain in the donor region between G1 and G3 after 1 hour (h), 2h, 3h, 7h, 8h and in the second day evening; between G1 and G2 after 2h and 3h, and between G2 e G3 only after the first hour. Pain intensity in the receptor area was statistically significantly between G1 and G3 after 1 and 2 hours (Kruskall-Wallys and LSD pos-test ; p<0.05). In addition, there was a lower ingestion of rescue medication in G2(1,05±1,39) and G3(1,52±1,74) than in G1(2,85±2,00) (p<0,05). The adoption of a preemptive medication protocol using etoricoxib or dexamethasone can be considered effective on pain prevention after mucogingival surgery.